RELATIONSHIP BETWEEN CONSUMPTION OF SIMPLE CARBOHYDRATES AND SERUM URIC ACID CONCENTRATION IN ADOLESCENTS - Arden, Pamela; Pusparini, Pusparini (HEARTY, 2025)
Indonesia is one of the countries with high uric acid levels that generally occur in adolescents. This condition is influenced by a number of factors, one of which is the consumption of simple carbohydrates. The aim of this study was to determine the relationship between consumption of simple carbohydrates and serum uric acid in adolescents. This study used a cross-sectional design, with as respondents 76 adolescents in the Impact Community Indonesia church, North Jakarta. The consumption pattern of simple carbohydrates was measured by filling the semi-quantitative food frequency questionnaire (SQ-FFQ), whereas serum uric acid was measured with the Autocheck instrument. Data were analyzed using SPSS version 23.0 at significance level of p < 0..05. Mean consumption of simple carbohydrates in male adolescents was 1839 grams and in female adolescents 1592 grams per month, whereas mean concentration of serum uric acid in male adolescents was 6.6 mg/dL and in female adolescents 5.2 mg/dL. The results of the Chi-Square test found a significant relationship between consumption of simple carbohydrates and serum uric acid concentration (p = 0.000). The conclusion of this study was that there was a significant relationship between consumption of simple carbohydrates and serum uric acid concentration in adolescents.